Technical skill training and assessment in dental education - Katsumi Uoshima; Nami Akiba; Masako Nagasawa (Elsevier, 2021)
Highly competent clinical practice requires cognitive, psychomotor and affective skills. Therefore, the ultimate goal of dental education is for practitioners to be competent in all of these domains. While many methods have been introduced to assess knowledge and non-technical skills, it is still very difficult for educators to assess technical skill.Assessment methods for technical skills are still not well established because it is very difficult to assure objectivity, validity and fairness. Nonetheless, technical skill is especially important in dental treatments, along with knowledge and attitude. The aim of this review was to summarize the methods of technical skill training in dental education and how they are assessed.This is a literature review. We searched PubMed MEDLINE using terms related to technical skill training and those assessment as of June 2020 and reviewed them.There have been many reports introducing methods of technical skill training and assessment, including the use of digital technology. However, no single assessment method had demonstrated validity of it. Technical skill training is very important in dental education and there are various ways of learning. The validity of current assessment methods is limited; therefore, a combination of several methods may achieve the best results.